STRATEGI PENINGKATAN MUTU RINTISAN MADRASAH UNGGUL: - Erlina Farida (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2015)
The presence of exemplary madrasa colors the existence of madrassas in Indonesia in the midst of modernized and globalized era. The existence of MTsN Yogyakarta I as a featured pilot school by the Ministry of Religious Affairs is admirable due to its quality as an excellent school based on the assessment of the MoRA Yogyakarta Province. This madrasa is able to accommodate the parents’ need to send their children to an excellent religious education and an excellent Islamic custom habituation. Various strategies have been undertaken by this madrasa to achieve a superior madrasa, such as: improving the quality educators, service quality, organizational culture, infrastructure, curriculum innovation and learning, especially the development of superior class to realize its excellence.